Doing Business with Rights Violating Regimes Corporate Social Responsibility and Myanmar's Military Junta - Holliday, Ian (Journal of business ethics, 2005)
Whether to do business with rights violating regimes is one of many dilemmas faced by socially responsible corporations. In this article the difficult case of Myanmar is considered. Ruled for decades by a closed and sometimes brutal military elite, the country has long been subject to informal and formal sanctions. However, as sanctions have failed to trigger political reform, it is necessary to review the policy options. The focus here is on the contribution socially responsible corporations might make to change. The article sketches contextual features of the case, examines the recent history and present pattern of business links with Myanmar, and assesses whether current approaches can stimulate reform. Concluding that they cannot, it considers fresh possibilities for corporate engagement. The argument is that socially responsible corporations, committed to improving individual life chances through engagement with developing societies, should undertake collaborative and principled direct investment in Myanmar. The underlying strategy and problems of codification and implementation are all analyzed. To close, the article contends that, by doing business with Myanmar's rights violating regime, multinational corporations can extend the frontiers of global corporate social responsibility.